Medial Gastrocnemius Flap for Reconstruction of the Extensor Mechanism of the Knee Following High-Energy Trauma. A minimum 5 year follow-up. Issue 8 (August 2016) - Hohmann, Erik; Wansbrough, Guy; Senewiratne, Serene; Tetsworth, Kevin
Abstract: Introduction: The purpose of this study was to assess the medium-term results of reconstruction of the extensor mechanism using the medial gastrocnemius while also providing soft tissue coverage. Materials and methods: This retrospective review consisted of a consecutive series of four patients (age 28–40 years) with complex high energy traumatic injuries to lower extremity including both soft tissue loss and disruption of the knee extensor mechanism. The medial gastrocnemius rotational flap was used to reconstruct the patellar tendon and restore soft tissue coverage simultaneously. Range of motion and extensor lag; functional recovery was judged by return to work and sports activity. Validated measures included the Oxford Knee Score, Knee Injury and Osteoarthritis Outcome Score, and the modified Cincinnati Score. Results: At the final follow up was 61.5 (57–66) months after reconstruction, the mean SF 12 physical component score ranged from 21.7 to 56.8 with a median of 55.3; the mental component from 42.8 to 60.7 with a median of 58.6. The KSS knee score ranged from 50 to 78 with a median of 68; the function score from 65 to 90 with a median of 85. The Oxford knee score ranged from 22 to 45 with a median of 33.5. The KOOS ranged from 28 to 82.7 with a median of 73.7 and the modified Cincinnati score from 38 to 82 with a median of 76.5. Knee range of motion ranged from 0 to 120°. Of the four patients three returned to working fulltime in their profession and returned to sports, including mountain biking and fitness training. Conclusions: For severe traumatic knee injuries with the combination of soft tissue defects and disruption of the extensor mechanism, the medial gastrocnemius flap provides an excellent reconstructive option to address both problems simultaneously. The results of this small case series support the use of this limb salvage technique.